Influence of patch load length on plate girders. Part I: Experimental research. (June 2019) - Markovic, N.; Kovacevic, S.
Abstract: An experimental research considering the behavior and ultimate strength of longitudinally stiffened plate girders subjected to localized edge loading in the plane of the web, a load case usually referred to as patch loading, is presented. Based on a literature review, the limitations of previous investigations are listed, which proved the need for additional experimental research. Part I of this research includes the main experimental test results, originally given in (Markovic, 2003 [1]), while in Part II the finite element modeling, verification of numerical models as well as results of an extensive parametric study will be presented. The driving force for performing this experimental campaign was to investigate the influence of patch load length on the ultimate capacity of longitudinally stiffened girders since this parameter has not been systematically studied. The influence of patch load length is thoroughly analyzed and results concerning the influence of longitudinal stiffeners are elaborated. The experiments are described in detail and the main conclusions of the experimental investigation are presented. It may be concluded that there is a significant influence of the length of patch load on the behavior and ultimate strength of the girders. The combined influence of increased patch load length and longitudinal stiffener can significantly increase the patch load resistance of plate girders. It can be concluded that the ultimate load of stiffened girders follows the ultimate strength of unstiffened ones under small patch load lengths. When a specific applied load length is reached, an appreciable strengthening effect can be obtained. Highlights: Larger patch load lengths produce higher ultimate strengths. Longitudinal stiffener can significantly increase the patch load resistance of plate girders. Ultimate load for unstiffened girders rises with a constant slope with respect to the patch load length. Ultimate strength of stiffened girders under small patch load lengths follows the ultimate strength of unstiffened ones. An appreciable strengthening effect can be obtained when a specific applied load length is reached.